Manual de estrategias metodológicas para la detección e intervención en trastornos de aprendizaje dirigido a docentes de educación general básica superior del Colegio Técnico Salesiano "Don Bosco" Kennedy - Pulla Miranda, Stephanie Michelle (2015)
The development of this product provides teachers of the Educational Institution, introductory tools and appropriate methodologies for TEA students. In order to facilitate the teaching-learning process that teachers provide considering the educational needs and abilities of young people. Thus materials, methodology, and active communication that teacher uses in the teaching process will guide the student to solve problems, meet educational goals and develop skills and learning skills. Teacher is one of the main actors in the teaching process, should encourage their students necessary tools to achieve decreasing differences. Current education is able to educate in and through diversity, it requires us to start thinking differently, in terms of teaching actively, seeking not to exclude students from their benefits. Mediation is considered an alternative conflict resolution tool, which is framed in a peace and democracy culture, the mediation purpose is communication. At Técnico Salesiano College "Don Bosco", the most specific learning disabilities showed during pre-internships were dyslexia, dysgraphia, and dyscalculia dysorthography, explaining them from their causes to diagnosis and intervention of each, in order to know teens characteristics and their learning difficulties. At the conclusion of the framework, it was necessary to analyze the educational community perception, using the communication tool: survey and also by observing institutional members during the investigation, we could know the prospects that they have with the elaboration of a support manual which facilitate assertive speech to the teens difficulties and needs in the learning process by teachers.